Navigating regulatory and policy challenges for AI enabled combination devices - Santra, Snigdha; Kukreja, Preet; Saxena, Kinshuk; Gandhi, Sanyam; Singh, Om V. (Frontiers in Medical Technology, 2024)
In recent years, the Artificial Intelligence (AI) has enabled conventional Combination Devices (CDs) to innovate in healthcare merging with technology sectors. However, the challenges like reliance on predicate devices in US Food and Drug Administration (FDA)'s 510(k) pathway, especially for perpetually updating AI are stressed. Though the European Union (EU)'s new Medical Device Regulations address software and AI, fitting adaptive algorithms into conformity assessments remains difficult. The urgent need for frameworks cognizant of AI risks like model degradation and data biases is emphasized. Insights from recalled devices and case studies elucidate challenges in regulatory navigation for manufacturers. Adaptive policy frameworks balancing patient safeguards and rapid innovation are proposed.Recommendations target regulators and policy makers, advocating global standards to enable safe, effective and equitable AI adoption. This article aims to examine AI-enabled combination device regulation, inspecting US and EU strategies as well as obstacles for manufacturers and regulators.